Introduction - Pajuelo Ramírez, Jaime (2017)
In the 21st century, the world is undergoing a series of changes known as transitional, which are reflected in the economic, demographic, epidemiological, environmental and even nutritional fields. This dynamic is given with some diversity in countries where in some countries it has already been installed for many years, while in others, such as ours, its presence occurs in large urban areas and to a lesser extent in rural areas.